Neoliberalism’s strategic attack on education: homeschooling (Práxis Educativa, 2024)
This article emerged from a concern about a proposal that has been part of the public educational debate since the 2000s with the advent of the Escola sem Partido movement [Non-partisan school], Home Education or homeschooling. Thus, the aim was to understand the relationship between the neoliberal doctrine and the education policy proposal for homeschooling. To this end, through the postulates of a bibliographic study, the theoretical basis of this article was predominantly based on Laval (2019) and Lockmann (2020). With that, it was possible to demonstrate and confirm the assertion that neoliberalism operates through strategies in the educational field, homeschooling being one of them. Therefore, education constitutes a very profitable market niche for capitalist exploitation.Keywords: Home education. Homeschooling. Neoliberalism.